COVID-19 pandemic-induced physical inactivity: the necessity of updating the Global Action Plan on Physical Activity 2018-2030 - H. Amini; S. Habibi; A. H. Islamoglu; E. Isanejad; C. Uz; H. Daniyari (Komiyama Printing Co. Ltd, 2021)
Abstract To prevent and reduce inactivity, the World Health Organization (WHO) designed a global plan called Global Action Plan on Physical Activity 2018-2030 (GAPPA) in 2017. In this plan and according to the state of physical activity in 2016, actions and goals were set. However, the world is facing a COVID-19 pandemic, which has affected various aspects of lifestyle, including physical activity. Some studies have shown that physical activity reduced during the pandemic. For this reason, the WHO should review the GAPPA and update goals and actions according to the state of physical activity in 2020.